Treatment of genital herpes using olive leaf extract - Lorzadeh, Nahid; Kazemirad, Yasaman; Kazemirad, Nastran (Wiley, 2021)
Genital herpes is one of the sexually transmitted diseases that is reported with a greater incidence of primary and secondary recurrence. In this study, olive leaf extract was used for its antiviral properties to treat the infection. The randomized-clinical trials using such a therapeutic approach are required in this field.
Keywords: Acyclovir; Antiviral; Genital Herpes; Infection; Olive Leaf Extract